A novel variant in PAX6 as the cause of aniridia in a Chinese family - X Jin; W Liu; LH Qv; WQ X; HB Huang (BMC Ophthalmology, 2021)
Abstract Background Aniridia is a kind of congenital human pan-ocular anomaly, which is related to PAX6 commonly. Methods The ophthalmic examinations including visual acuity, slit lamp and fundoscopy examination were performed in a Chinese aniridia pedigree. The targeted next-generation sequencing of aniridia genes was used to identify the causative mutation. Results A novel heterozygous PAX6 nonsense mutation c.619A > T (p.K207*) was identified in the Chinese autosomal dominant family with aniridia. Phenotype related to the novel mutation included nystagmus, keratopathy, absence of iris, cataract and foveal hypoplasia. Conclusions The novel nonsense variation in PAX6 was the cause of aniridia in this family, which expanded the spectrum of the PAX6 mutation.